Environmental policy : creation and implementation of an environmental policy in Iceland - Kristján Leifur Sverrisson 1996-; Rósa Björk Pétursdóttir 1997- (2021)
Environmental policies are tools that can have positive effects on environmental, social and economical factors of companies. The implementation of these policies can be a complicated process, but in the long run benefits companies with reduced operating costs, improved company image and increased goodwill. Environmental management systems and certifications can help in the creation and implementation of environmental policies, as well as increase trustworthiness of the operations that companies undertake while eliminating the risk of greenwashing. An internet survey was published to research the effects that environmental affairs of companies had on consumers, whether consumers would care if the companies they choose to do business with were environmentally friendly and socially responsible or not. The survey revealed that most parties were impartial to the survey questions, citing that it had a neutral impact on their buying decisions. However, the survey also revealed that many consumers are impacted in their buying decisions, based on the affairs of the companies they do business with. If companies show bad practices in environmental and social affairs, it can cause them to lose customers according to the results of the survey. In-depth interviews were conducted, both external and internal. External interview participants were specialists in sustainability and environmental issues. Internal interview participants were mostly managers, chosen because of their oversight of the company‘s procedures and knowledge. In addition, lower ranked employees, who might have good insights on the day to day operations were chosen for interviews. The main findings from our qualitative data is that Domino‘s is doing very well on the social front, but can improve on the environmental aspects of their operation. Domino‘s can be a leading force in the restaurant industry and motivate other companies to improve their environmental affairs. Keywords: Environmental Policy, Goodwill, Certifications, Environmental management system, ...